2013
DOI: 10.1386/padm.9.1.135_1
|View full text |Cite
|
Sign up to set email alerts
|

Making do and making new: Performative moves into interaction design

Abstract: It is now possible to creatively explore movement data and this article queries how we may engage with movement data in order to explore the inherent dynamics in computational data when sourced from the expressive body. It discusses how designing intermediary digital tools may reveal the potentials and particularities of movement data. It proposes Malleability, Visuality and Ambiguity as central to the design of digital tools as these may be put to work to tease out the performative potential of movement data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Motion and physiological data collected through input technologies has mostly been used to obtain insights from the dancer's body, resulting in sonification [3], visualisation [23], and/or interaction with any other choreographic elements (e.g. scenic design [35], light design [8], costumes [6]).…”
Section: Interactive Technology In Dance Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Motion and physiological data collected through input technologies has mostly been used to obtain insights from the dancer's body, resulting in sonification [3], visualisation [23], and/or interaction with any other choreographic elements (e.g. scenic design [35], light design [8], costumes [6]).…”
Section: Interactive Technology In Dance Performancementioning
confidence: 99%
“…sensor technology [21]) and outputs (e.g. display strategies [23]). Related studies have analysed dance performance from a segmented perspective, mainly focusing on movement characteristics or display approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Both these aspects, the engagements and the refinement, are in part achieved by merely trying movements out, through repeating and rehearsing movements. This can be seen as a material exploration akin to sketching with a pencil or modelling with clay (Hansen, 2013). Such material explorations are at the core of creative practices, and we argue, are crucial in building a discourse on technology, interaction and movement.…”
Section: Why This Kind Of 'Making Strange'?mentioning
confidence: 98%
“…Sync does this by visualising the velocity or the rate of change in the position of a body part (see Figure 3 and 4). Based on the performers extensive body-based practice, we were able to open up the examination of the role of this digital material, that is movement data, and in particular the creative and decisive decision taken in data handling (Hansen, 2013). We found that working with real-time 1:1 images created an engagement whereby we could question the pre-emptive requirements of computation to decide on values, as the dynamic visualizations allowed variation and individuation.…”
Section: Syncmentioning
confidence: 99%
“…Copyright is held by the owner/author(s). C&C '13, Jun 17-20 2013 The workshop invites a sharing of the process of designing for technology based on the emerging experiential and computational models that describe and represent movement knowledge [6,8,9,10,13,15,16,19,22,23]. …”
mentioning
confidence: 99%